Biodegradation of Tetracycline Antibiotic by Laccase Biocatalyst Immobilized on Chitosan-Tripolyphosphate Beads - Jeong, D.; Choi, K. Y. (Applied Biochemistry and Microbiology, 2020)
Abstract: In this study, biodegradation of tetracycline, which is one of the most commonly used antibiotics, was investigated. In order to convert tetracycline into inactive oxidative metabolites, laccase immobilized onto rigid tripolyphosphate-treated chitosan beads was utilized. For immobilization, chitosan surfaces were activated with glutaraldehyde-linker reagents after tripolyphosphate treatment. The glutaraldehyde-linked rigid chitosan beads showed the higher immobilization capacity of laccase, providing thermostability, reusability, and the higher tetracycline transformation activity. Subsequently, synthetic mediators, including 2,2'‑azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and lignophenolic mediators like violuric, syringic and ferulic acids, 1-hydroxybenzotriazole, and vanillin, were investigated to activate laccase as electron mediators with KI assistance. Among them, the immobilized laccase showed highest tetracycline antibiotic inactivation activity when ABTS was used as a mediator. In the presence of KI, violuric and ferulic acids, 1-hydroxybenzotriazole and vanillin functioned as laccase mediators and inactivated tetracycline almost completely, however, the effect was not observed when they did individually. Finally, Vmax of the immobilized laccase was determined as 76.3 ± 4.3 µmoles mg–1 min–1 against tetracycline, which was 2-fold higher than that of the free enzyme. These results will provide novel insights into laccase-based removal of non-biodegradable organic matter.
Keywords: biodegradation; chitosan immobilization; electron mediator; laccase; tetracycline